Indivíduo, valores e decisão em Max Weber - Fiscina, Lênin Cesar Freire (2015)
The aim of the dissertation is the process of rationalization in Max Weber, specifically social rationalization, not referring only to the institutionalization of the state and the company, but the institutionalization of the University as legitimate core of science. And in cultural terms do not restrict the differentiation and autonomy of the spheres, but the process by which science and its values extend beyond its institutional boundaries through scientific rationalization. Our object will then be the decision-making process that enables the discussion and critique of values, the formation of a modern consciousness, the sociological significance of the city and urban culture, the communicative record that we can glimpse in the unfinished work of the sociologist; therefore carefully analyze the Weberian decisionism and its historically determined forms that are accompanied in modernity by the ethics of responsibility.